1995
DOI: 10.1530/eje.0.1330180
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density in adults with growth hormone (GH) deficiency: increased bone turnover during 12 months of GH substitution therapy

Abstract: To evaluate the consequences of growth hormone (GH) deficiency on bone mineral density and to evaluate the effects of GH substitution therapy, 68 adults (25 females and 43 males) aged 22-61 (mean 44.2 +/- 1.2) years with GH deficiency (GHD) were studied. Fifty-eight patients had panhypopituitarism, three had isolated GHD and in seven patients at least one additional pituitary function was affected. Twenty-one patients had childhood onset GHD. The patients were randomized to receive either GH in daily injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 18 publications
7
73
0
3
Order By: Relevance
“…In fact, long-term administration of rhGH has been shown to signi®cantly improve bone mineralization in GH de®cient adults, 34 who display reduced BMD and increased risk for fracture. 35 In the present study, a tendency of the serum markers of bone turnover (AP bone isoenzyme, serum osteocalcin and urinary hydroxyproline) to increase was observed in obese patients treated with rhGH but not in energy-restricted placebo-treated patients. Moreover, rhGH treatment appeared to prevent, in our obese women, a diet-related reduction of urinary calcium.…”
Section: Discussionsupporting
confidence: 42%
“…In fact, long-term administration of rhGH has been shown to signi®cantly improve bone mineralization in GH de®cient adults, 34 who display reduced BMD and increased risk for fracture. 35 In the present study, a tendency of the serum markers of bone turnover (AP bone isoenzyme, serum osteocalcin and urinary hydroxyproline) to increase was observed in obese patients treated with rhGH but not in energy-restricted placebo-treated patients. Moreover, rhGH treatment appeared to prevent, in our obese women, a diet-related reduction of urinary calcium.…”
Section: Discussionsupporting
confidence: 42%
“…The studies which have frequently been designed as open observational follow-up to short term randomised trials, uniformly tend to show an initial significant decline of BMD or BMC at several sites during GH therapy followed by an increase in BMD from 6 months onwards (9 -16). However, total body BMD was shown to remain significantly reduced after 12 months of GH treatment (17). In a Finnish multicentre study (15) subanalysis revealed that significant treatment effects were found only in patients who were osteopenic at baseline and, further, that treatment response was significantly more pronounced in male than in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, GH substitution therapy should improve bone mineralisation and reduce fracture risk in these patients. An increase of BMD and BMC following GH treatment has been reported in several (9 -16) but not all (17) open trials. However, except for one study (18,19), the verification of such findings in randomised, placebo-controlled, double blinded trials with appropriate treatment doses of GH has not been possible.…”
Section: Introductionmentioning
confidence: 96%
“…15,17 Treatment of GHD patients with GH dosedependently increases bone turnover as judged by biochemical bone markers. [19][20][21][22][23][24] Due to the dynamics of bone remodelling (bone resorption preceding bone formation), increases in bone resorptive and formative markers are observed after three and six months substitution, respectively. Although the effects of GH on bone turnover are consistent and sustained during long-term substitution, the effects on bone mass have been more elusive due to short duration of treatment period.…”
Section: S T U D I E S I N P a T I E N T S W I T H A O -G H Dmentioning
confidence: 99%